IDENTIFIKASI BAKTERI AEROB PADA LINDI HASIL SAMPAH DAPUR DI DUSUN SUKUNAN YOGYAKARTA - Khamid, Mohamad Abdul; Mulasari, Surahma Asti (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2012)
Background : Various human activities will generate waste. Trash can pollute the environmentand as home to a wide range of diseases that can reduce the degree of human health, so thatthe waste be managed properly. Sukunan village was already implementing community-basedintegrated waste processing were independent and productive, clean and beautiful environmentthat involves all citizens in the implementation. The kitchen garbage management in thesukunan village is included in the composter to be composted with the results of liquid bybacterial degradation of organic material in the form of leachate. Leachate by the communitySukunan village used for liquid fertilizer plant and sold. The purpose of this study determined thegenus of aerobic bacteria in the leachate of kitchen garbage result in Sukunan village.Method : This research type was the descriptive research with laboratory test. The sample inthis study was leachate of Sukunan village kitchen garbage result. The study was conducted intwo places, in the Public Health Laboratory of Ahmad Dahlan University and in the YogyakartaHealth Laboratory Central. The results of data analysis was described in descriptive studies andpresented in tabular and narrative.Results : Identification of aerobic bacteria was carried in the Public Health Laboratory of theAhmad Dahlan University get the bacteria that approached the characteristics of the genusPseudomonas, Bacillus, and Escherichia / Salmonella / Aeromonas / Chromobacterium, whilethe results of identification carried out in the Health Laboratory Central in Yogyakarta got thebacterial genus such as Streptococcus (species : Enterococcus faecalis), Escherichia (species:Escherichia coli), Pseudomonas (species: Pseudomonas putrifaciens) and Proteus (species:Proteus vulgaris).Conclusion : There has aerob bacteria in the leachate of kitchen garbage results in theSukunan Village, Yogyakarta.Keywords : Aerobic Bacteria, Leachate